The Effect of Deep Breathing Exercise on Lung Capacity of Dyspepsia Patients at the Clinics Pada Idi Medical Center and Prima Physio Sakura, Makassar City - Wutsqa, Andi Urwatul; Ita Rini; Pujiningrum, Andi Rahmaniar Suciani; Muthmainnah, Meutiah (Physiotherapy, Exercise, and Rehabilitation Sciences Journal, 2026)
Aims: Dyspepsia is a digestive disorder that can cause increased intra-abdominal pressure, which has an impact on decreasing lung capacity. One of the non-pharmacological interventions that can be used to increase lung capacity is deep breathing exercise (DBE). This deep breathing exercise is known to be able to increase lung elasticity and gas exchange efficiency. Methods. This study used a quasi-experimental design with pre-test and post-test in the experimental and control groups. The sample consisted of 22 dyspepsia patients divided into two groups: 11 people in the intervention group who were given deep breathing exercise for 9 sessions and 11 people in the control group. Lung capacity was measured using a peak flow meter before and after the intervention. Data analysis was performed using the paired sample t-test. Results. The results showed a significant increase in lung capacity in the intervention group after being given deep breathing exercise with the mean PEFR increased from 224.5 L/min to 335.4 L/min (p=0.001). In contrast, in the control group there was no significant difference before and after the period without intervention (p=0.157). Conclusion. Deep breathing exercise has been shown to have a significant effect in increasing lung capacity in patients with dyspepsia. This exercise can be recommended as an additional therapy in dyspepsia management to improve respiratory function and quality of life in dyspepsia patients.